(untitled) (Observatorio Económico, 2013)
Education, as an industry, is organized vertically: primary school students are inputs used to ‘produce’ secondary school students, and the latter are, in turn, the factor used to ‘produce’ university-level knowledge and skills. This hierarchical organization of the education industry has at least two basic economic consequences. The first is that the amount of human capital, measured by the number of people, decreases as we move up through the educational levels. Continue reading...